PENGARUH PEMBELAJARAN KOOPERTIF TIPE STAD TERHADAP KEMAMPUAN PEMAHAMAN DAN KOMUNIKASI MATEMATIS SISWA SEKOLAH DASAR - Siti Fitriani, Rayi (STKIP Subang, 2015)
Examined the differences in mathematical ability of understanding and communication between students and Cooperative Learning STAD and students in hands-on learning. The subjects were students of class IV SDN Sarimulya II Cikampek. The study concluded: 1) The ability of the final mathematical understanding of students who received different STAD cooperative learning with the ability of students who received direct instruction. 2) The ability of mathematical communications students getting the same STAD cooperative learning with students getting hands-on learning. 3) Increased understanding of the mathematical ability of students who received STAD cooperative learning does not differ greatly from the ability of the students who received direct instruction. 4) Improving students' mathematical communication skills that got STAD cooperative learning significantly better than students who received direct instruction.